Involvement of MAPK/NF-κB Signaling in the Activation of the Cholinergic Anti-Inflammatory Pathway in Experimental Colitis by Chronic Vagus Nerve Stimulation - Sun, Peng; Zhou, Kewen; Wang, Sheng; Li, Ping; Chen, Sijuan; Lin, Guiping; Zhao, Yan; Wang, Tinghuai (PLOS ONE, 2013)
BackgroundAutonomic nervous system dysfunction is implicated in the etiopathogenesis of inflammatory bowel diseases (IBD). Therapies that increase cardiovagal activity, such as Mind-Body interventions, are currently confirmed to be effective in clinical trials in IBD. However, a poor understanding of pathophysiological mechanisms limits the popularization of therapies in clinical practice. The aim of the present study was to explore the mechanisms of these therapies against 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats using a chronic vagus nerve stimulation model in vivo, as well as the lipopolysaccharide (LPS)-induced inflammatory response in human epithelial colorectal adenocarcinoma cells (Caco-2) by acetylcholine in vitro. Methods and ResultsColitis was induced in rats with rectal instillation of TNBS, and the effect of chronic VNS (0.25 mA, 20 Hz, 500 ms) on colonic inflammation was evaluated. Inflammatory responses were assessed by disease activity index (DAI), histological scores, myeloperoxidase (MPO) activity, inducible nitric oxide synthase (iNOS), TNF-α and IL-6 production. The expression of Mitogen-activated protein kinases (MAPK) family members, IκB-α, and nuclear NF-κB p65 were studied by immunoblotting. Heart rate variability (HRV) analysis was also applied to assess the sympathetic-vagal balance. DAI, histological scores, MPO activity, iNOS, TNF-α and IL-6 levels were significantly decreased by chronic VNS. Moreover, both VNS and acetylcholine reduced the phosphorylation of MAPKs and prevented the nuclear translocation of NF-κB p65. Methyllycaconitine (MLA) only reversed the inhibitory effect on p-ERK and intranuclear NF-κB p65 expression by ACh in vitro, no significant change was observed in the expression of p-p38 MAPK or p-JNK by MLA. ConclusionVagal activity modification contributes to the beneficial effects of the cholinergic anti-inflammatory pathway in IBD-related inflamed colonic mucosa based on the activation of MAPKs and nuclear translocation of NF-κB. Our work may provide key pathophysiological mechanistic evidence for novel therapeutic strategies that increase the cardiovagal activity in IBD patients.